2019
DOI: 10.1186/s12906-019-2494-8
|View full text |Cite
|
Sign up to set email alerts
|

What has been the impact of the Traditional Herbal Registration (THR) scheme in the UK on information provided with herbal products bought over the counter?

Abstract: Background In 2011 there was a strengthening of European Union (EU) legislation on the licencing of herbal products which, in the UK, resulted in the introduction of the Traditional Herbal Registration (THR) scheme. This scheme sets out standards for the safety and quality of herbal medicines and includes the provision of information to the customer on the safe use of the product. The aim of this study is to replicate a survey undertaken in 2011, prior to the implementation of the THR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In line with the THR scheme, in addition to performing quality and safety checks, "plausible efficacy" based on evidence of longstanding use and experience is sufficient to prove the product's efficacy. A study that evaluated the impact of the THR scheme in the UK prior to and after its implementation revealed that an increase in the quality of information provided with HMs was achieved (18). As the THR scheme is associated with appropriate pre-marketing evaluation, and more complete information than the dietary supplements classification, it is proposed that in addition to the choice of applying for a product license of the type needed to manufacture "conventional" products and providing evidence of clinical efficacy, the THR scheme should be implemented in the Kuwaiti DRA (Figure 1).…”
Section: The Recommendations Proposed Definition and Classificationmentioning
confidence: 99%
“…In line with the THR scheme, in addition to performing quality and safety checks, "plausible efficacy" based on evidence of longstanding use and experience is sufficient to prove the product's efficacy. A study that evaluated the impact of the THR scheme in the UK prior to and after its implementation revealed that an increase in the quality of information provided with HMs was achieved (18). As the THR scheme is associated with appropriate pre-marketing evaluation, and more complete information than the dietary supplements classification, it is proposed that in addition to the choice of applying for a product license of the type needed to manufacture "conventional" products and providing evidence of clinical efficacy, the THR scheme should be implemented in the Kuwaiti DRA (Figure 1).…”
Section: The Recommendations Proposed Definition and Classificationmentioning
confidence: 99%
“…HM are regulated through the Directive 2001/83/EC. This Directive sets out requirements for registration of HM to ensure maximum consumer protection including the following: meeting standards of quality and safety and providing sufficient evidence of traditional use (2001/83/EC) (Dickinson et al 2019). Following the publication of this legislation, the Traditional Herbal Registration (THR) Scheme was set up by the UK MHRA, which sets out standards for the safety and quality of HM and includes the provision of information to the customer on the safe use of the product (Dickinson et al 2019;MHRA 2019aMHRA , 2019b.…”
Section: ]mentioning
confidence: 99%
“…Following the publication of this legislation, the Traditional Herbal Registration (THR) Scheme was set up by the UK MHRA, which sets out standards for the safety and quality of HM and includes the provision of information to the customer on the safe use of the product (Dickinson et al . 2019; MHRA 2019a, 2019b).…”
Section: Regulatory Framework For Botanical Food Supplements and Herbmentioning
confidence: 99%
“…Indeed, plant extracts can be very effective therapeutically, but some can reveal themselves to be toxic with a risk of serious poisoning (Chanda et al ., 2015; Ngbolua et al ., 2011a, b; Izzo, 2004; Whitto et al ., 2003); moreover, mid-term to long-term toxicities represent particular risks as they are hardly detected by tradipraticians (Williamson et al, 2015). In the European Union, a safe use, correctly documented over a sufficient time, is considered to yield a plausible indication of innocuity, and forms the basis for marketing a traditional herbal product (Dickinson et al, 2019; HMPC, 2018). However, in many traditional medicines, and especially in developing countries, the use and safety of herbal products is hardly documented.…”
Section: Introductionmentioning
confidence: 99%